1995
DOI: 10.1128/jvi.69.9.5705-5715.1995
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between herpes simplex virus immediate-early proteins during infection: gene expression as a consequence of ICP27 and different domains of ICP4

Abstract: Two of the five immediate-early gene products, ICP4 and ICP27, expressed by herpes simplex virus type 1 have profound effects on viral gene expression and are absolutely essential for virus replication. Functional interactions between ICP4 and ICP27 may contribute to establishing the program of viral gene expression that ensues during lytic infection. To evaluate this possibility, viral mutants simultaneously deleted for ICP27 and defined functional domains of ICP4 were constructed. These mutant viruses allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 77 publications
5
59
0
2
Order By: Relevance
“…9) (13,38,71). Previous studies demonstrated that ICP27 is required for the expression of HSV early and late genes in productive infections (65,67,73). Therefore, significant decreases in the accumulation of ICP27 would be predicted to result in defects in the accumulation of early and late virus proteins and in virus growth.…”
Section: Fig 5 Southern Blot Analysis Of Wild-type and Recombinant mentioning
confidence: 99%
See 1 more Smart Citation
“…9) (13,38,71). Previous studies demonstrated that ICP27 is required for the expression of HSV early and late genes in productive infections (65,67,73). Therefore, significant decreases in the accumulation of ICP27 would be predicted to result in defects in the accumulation of early and late virus proteins and in virus growth.…”
Section: Fig 5 Southern Blot Analysis Of Wild-type and Recombinant mentioning
confidence: 99%
“…ICP27, another essential protein, is required for the expression of ␤ and ␥ genes during the HSV life cycle. This protein appears to act primarily at the posttranscriptional level (47,59,62,65,67,73); however, recent evidence supports a more direct role for ICP27 in the regulation of gene expression (55).…”
mentioning
confidence: 99%
“…The titers of infectious virus in stocks of all the ts mutant viruses were determined simultaneously on Vero cell monolayers at 34ЊC, and stocks of nonsense, deletion, and other mutant viruses were titrated on monolayers of the appropriate cell lines at 37ЊC. The ICP4-ICP27 double-mutant virus, d92, was derived by recombination between d120 and 5dl1.2 (36). Thus, d92 contains the d120 mutant ICP4 allele at both ICP4 loci and the 5dl1.2 mutant ICP27 allele at the single ICP27 locus and was propagated in the E26 cell line, which provides comparable levels of ICP4 and ICP27.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Since transactivators function in the nucleus, the cytoplasmic localization of ICP0 in ICP4 mutant virus-infected cells would prevent ICP0 from performing its transactivating function. On the other hand, even though ICP0 localizes exclusively within the nucleus, the expression of E and L genes is more restricted in d92-infected cells than in cells infected with either d120 or 5dl1.2 (36). This observation suggests that the inability of ICP0 to activate the expression of E and L genes in ICP4 mutant virus-infected cells is not due solely to the cytoplasmic localization of ICP0 and that other factors, perhaps including ICP4 and/or ICP27, may also be involved in the control of the transactivating activity of ICP0 or the activities of the promoters of E and L genes in the context of the viral genome.…”
Section: Vol 70 1996mentioning
confidence: 99%
“…IE63 plays a key role in the switch from early to late gene expression (37,39), and this multifunctional protein has both trans-repressor and trans-activator functions (11,30,43,44). Transfection studies have demonstrated that IE63 acts synergistically with IE pro-teins IE175 and IE110 to repress expression from IE and early promoters and activate expression from late promoters (11,30,43); IE63 also affects the cellular localization of these two IE proteins (41,44). At the posttranscriptional level of gene regulation, enhancement of gene expression correlates with the ability of IE63 to stimulate 3Ј processing (28,29,42) at certain poly(A) sites whereas the repressor function is associated with an inhibition of splicing.…”
mentioning
confidence: 99%